Redefining Jihad in Leila Aboulela's The Kindness of Enemies (2015) - Abiyyah Haniya Zahra (Muslim English Literature, 2022)
Edward Said's Orientalism highlights how Islam and Muslims in the East were framed and highlighted negatively in Western countries, creating prejudice and a negative image of their culture, rituals, and religion. Arguably, the 9/11 and 7/7 tragedies have increasingly raised sentiments against Islam. Moreover, Muslims and Jihad are seen as terrorists, violent, and suicide bombings. This research aims to undermine the negative images of Jihad by examining Leila Aboulela's The Kindness of Enemies through its characters lived post-9/11 and 7/7. The method used in this study is Close Textual Analysis with the framework of postcolonial studies followed by secondary sources from scientific journals, video lectures, and books. The results found that the novel reveals the meaning of Jihad that developed after 9/11 focused on the character of Oz, who understands that Jihad is a great activity and is closely related to war. Moreover, stereotypes against Muslims have left Muslims limited free space to show their true selves. Furthermore, this research finds that Jihad should be an internal struggle for the individual against lust and away from evil temptations.